Education Based on Wahdatul 'Ulum in the Qur'an - Sufiana; Harmaini; Yusniar; Abbas (Konsultan Jurnal Ilmiah Indonesia, 2026)
Contemporary Islamic education is often faced with the challenge of dualism and dichotomy between religious knowledge (ulum ad-din) and general/worldly knowledge (ulum ad-dunya). This separation results in the birth of an educated generation with a split personality, namely proficient in science and technology but lacking spiritual values, or conversely, deeply immersed in religious knowledge but stuttering in responding to the challenges of the times. This article aims to explore and reconstruct the concept of holistic and integrative Islamic education based on the paradigm of Wahdatul 'Ulum (Unity of Knowledge) sourced from the Qur'an. This research uses a library research method, specifically with a directed exploratory approach that systematically utilizes library sources as the main data base. The research process involves an in-depth examination of various written materials through critical reading and analytical review to comprehensively answer the research problem. Data sources consist of authoritative references such as books, scientific journals, classical and contemporary works, and academic articles relevant to the concept of education based on wahdatul 'ulum. Through this methodological framework, this research aims to synthesize and interpret the theoretical perspectives and insights of the Qur'an related to knowledge integration. The discussion presented in this article ultimately shows that the Al-Qur'an contains a number of verses that reflect and support the principles of education based on wahdatul ulum, indicating that the integration of religious knowledge and science has been deep in the world view of the Al-Qur'an.